Iron-catalyzed C(sp(2))-H alkylation of indolines and benzo[h]quinoline with unactivated alkyl chlorides through chelation assistance - Jagtap, Rahul A.; Samal, Pragnya Paramita; Vinod, C. P.; Krishnamurty, Sailaja; Punji, Benudhar (ACS Catalysis, 2020)
Regioselective C-H bond alkylation of indolines and benzo[h]quinoline with a wide range of unactivated and highly demanded primary and secondary alkyl chlorides is accomplished using a low-cost iron catalyst. This reaction tolerates diverse functionalities, such as C(sp(2))-Cl, fluoro, alkenyl, silyl, ether, thioether, pyrrolyl, and carbazolyl groups including cyclic and acyclic alkyls as well as alkyl-bearing fatty-alcohol and polycyclic-steroid moieties. The demonstrated iron-catalyzed protocol proceeded via either a five-membered or a six-membered metallacycle. Intriguingly, the C-7-alkylated indolines can be readily functionalized into free-NH indolines/indoles and tryptamine derivatives. A detailed mechanistic investigation highlights the participation of an active Fe(I) catalyst and the involvement of a halogen-atom transfer process via a single-electron-based mechanism. Deuterium labeling and kinetics analysis indicate that the C-H metalation of indoline is the probable turnover-limiting step. Overall, the experimental and theoretical studies supported an Fe(I)/Fe(III) pathway for the alkylation reaction comprising the two-step, one-electron oxidative addition of alkyl chloride.
Keywords: alkyl chlorides; Alkylation; C-H activation; chelation assistance; indolines; iron

Hybrid pincer (PNN)Ni(II) complex catalyzed selective C-H alkylation of pyridones using unactivated alkyl chlorides - Verma, Suryadev K.; Samal, Pragnya Paramita; Pradhan, Chandini; Pandey, Dilip K.; Krishnamurty, Sailaja; Punji, Benudhar (ACS Catalysis, 2025)
The use of readily accessible unactivated alkyl chlorides in the alkylation reaction to install valuable alkyl and methyl motifs into privileged heterocycles is an underdeveloped area. Herein, we report the regioselective C-H alkylation of diverse pyridones employing challenging unactivated alkyl chlorides as coupling partners, enabled by a strategically developed quinolinyl-based pincer (Ph2PNNQ)Ni(II) complex. The air-stable nickel catalyst is highly effective for the selective alkylation of functionalized 2-pyridones with both primary and secondary alkyl chlorides as well as for the unexpected C6 methylation, furnishing a wide range of 6-alkyl-2-pyridone scaffolds (78 examples). Remarkably, the alkyls bearing biologically and pharmacologically significant motifs, such as pterostilbene, nonyl phenol, sesamol, estrone, vitamin E, stigmasterol, cholesterol, and diosgenin, were compatible under this catalytic approach. The insights into the mechanism suggest that the alkylation reaction follows a Ni(II)/Ni(III)/Ni(IV) pathway involving the crucial two-step, one-electron oxidative addition of alkyl chloride. Several control studies, kinetics, and EPR analyses were performed to understand the detailed reaction pathway, further supported by density functional theory calculations.
Keywords: alkyl chlorides; C-H/C-Cl activation; hybrid pincer ligand; Mechanism; Nickel; pyridones